The Optimization of Legal Protection for Land Buyers in Buying and Selling Disputed Land - Rusdiyanto Rusdiyanto (Sultan Agung Notary Law Review, 2022)
Land in human life has an important function, therefore the law is tasked with providing legal protection and legal certainty for land buyers. Land that is in a state of dispute often creates problems for land buyers who lack information on the status of existing land. So that in reality the practice of buying and selling land often ignores existing consumer protection. Therefore, writing this article aims to discuss the relevance of the value of justice in consumer protection in buying and selling land. As for this writing using sociological juridical method. Based on the research conducted, it was found that the data is in the form of protection for buyers who have paid off in the sale and purchase of troubled land is not fair, this is due to the legal culture of sellers who are often dishonest regarding land status, and there are third parties related to the seller who also claim rights to a land that is also to the detriment of the buyer. The existence of efforts through the judiciary in its development is quite long and expensive. The lack of assurance of legal certainty and legal protection for troubled land buyers will ultimately undermine the principle of legal objectives according to Islam and at the same time the mandate of the Pancasila and the 1945 Constitution of the Republic of Indonesia, this will of course violate social justice for all Indonesian people.